Improvement of the competitive program of woman’s pair in acrobatics by means of choreography at a stage of the specialized basic preparation - Кизім, Петро Миколайович; Луценко, Лариса Сергіївна; Батєєва, Наталія Петрівна (Slobozhanskyi Herald of Science and Sport, 2016)
Kyzim P., Lutsenko L. Batieieva N. Purpose: to prove experimentally the technique of improvement of the competitive program of woman’s pair in acrobatics by means of choreography at a stage of the specialized basic preparation. Material & Methods: the following methods of the research were used: theoretical analysis and synthesis of data of special scientific and methodical literature; pedagogical supervision; pedagogical testing; methods of mathematical statistics. 10 competitive programs of woman’s pair in acrobatics are analyzed before and after the pedagogical experiment. Results: the estimated results of the technique of execution of the competitive program of each woman’s pair separately were received on the basis of a rating scale of criterion of implementation of the competitive program of woman’s pair in acrobatics (Rules of FIG, 2013–2016). The dynamic of the level of the competitive program of each woman’s pair separately is defined. Conclusions: it is established that additional resources of choreography influence significantly the level of the competitive program of woman’s pair in acrobatics at a stage of the specialized basic preparation.